PENGARUH PENEMPATAN DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN PADA PT. GRAMEDIA ASRI MEDIA KUPANG - LUKAS MA; TRI SURIS LESTARI (Universitas Boyolali, 2018)
Luke Ma. Thesis, 2017. The influence of placement and promotion of office on the performance of employess of PT. Gramedia Asri Media Kupang. Supervisor: Try Suris Lestari, S.Kom.,MM. The problem in this research is placement data and promotion position at PT. Gramedia Asri Media Kupang is not in accordance with the standards set by Nasional Gramedia in KPI rules (key performance indicator), KPI/STD/GAM/02/2011 for 2012-2016. The formulation of the problem in this study is whether the placement and promotion of positions partially and simultaneously significant effect on employee performance at PT. Gramedia Asri Media Kupang in 2012-2016? Based on the formulation of the problem, the purpose of this study is to determine the magnitude of the effect of placement and promotion of positions partially and simultaneouslly on the performance of employees at PT. Gramedia Asri Media Kupang. The data needed in this study are primary data and secondary data obtained by way of distributing questionnaires, interviews, and study documentation. Data were analyzed statistically by using multiple linear regression technique which was processed with SPSS program version 20.00. The result of data analysis shows the influence of job placement and promotion on employee performance shown by coefficient of determination ( ) equal to 86,1% and the rest 13,9% influenced by other factors like work motivation, employee compesation, discipline level, leadership style, employee and other employee loyalty. Based on the results of data analysis suggested to the management of PT. Gramedia Asri Media Kupang for the placement process is expected to pay attention to the elements of education level, working knowledge, work skilss, and work experience, as well as in the promotion phase of office to pay attention to the rules for its assesment given objectively and effectively through carring, credible, competen, competetive and customer delight. So it will be very useful to improve employee work performance. Furthermore, to other researchers are expected to conduct further research to determine the performance of employees at PT. Gramedia Asri Media Kupang such as work motivation, employee compesation, discipline level, leadership style, employee work loyalty that can support the results of this study.